Pengaruh Pendekatan Terapeutik Perawat Terhadap Tingkat Kecemasan Anak Prasekolah - Rischa Hamdanesti (Barongko: Jurnal Ilmu Kesehatan, 2026)
Background: Children undergoing treatment at health facilities often experience anxiety due to unfamiliar surroundings, medical procedures, and separation from their parents. Unresolved anxiety can have a negative impact on children's psychological well-being and hinder the treatment process. The therapeutic approach of nurses is one non-pharmacological intervention that can help reduce children's anxiety levels through empathetic communication, a friendly attitude, and providing a sense of security. Objective: This study aims to determine the effect of nurses' therapeutic approach on the anxiety levels of preschool children. Method: This study used a quantitative design with a pre-experimental one-group pretest–posttest approach. The study sample consisted of 30 children undergoing preventive treatment in the pediatric ward of Hospital X, selected using purposive sampling. The children's anxiety levels were measured using a child anxiety observation instrument before and after the nurses' therapeutic approach was administered. Data analysis was performed using a Paired T-test with a significance level of α = 0.05. Results: The results showed a significant decrease in children's anxiety levels after receiving therapeutic care, with a p-value < 0.05. Conclusion: The therapeutic approach of nurses has a significant effect on reducing children's anxiety levels. This approach needs to be applied consistently in childcare to support children's comfort and psychological well-being during treatment.